2020
DOI: 10.1099/ijsem.0.003838
|View full text |Cite
|
Sign up to set email alerts
|

Description of Erysipelothrix piscisicarius sp. nov., an emergent fish pathogen, and assessment of virulence using a tiger barb (Puntigrus tetrazona) infection model

Abstract: A recently described emergent disease of ornamental fish has been associated with an Erysipelothrix species positive for the surface protective antigen (spa) C gene. Whole genome sequencing was performed on five spaC Erysipelothrix isolates from diseased ornamental fish. In addition, these spaC Erysipelothrix isolates were compared to spaA-, spaB- and other spaC-positive Erysip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 32 publications
0
60
0
Order By: Relevance
“…nov., which have often been isolated from food-producing animals and ornamental fish [19], respectively, can cause substantial illness in humans. The serovars reported in these species are serovars 3,7,10,14,15,16,20,22 and 23 for E. tonsillarum [20], and serovars 5, 9, 10 and 18 for E. piscisicarius sp. nov [11,19,20].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…nov., which have often been isolated from food-producing animals and ornamental fish [19], respectively, can cause substantial illness in humans. The serovars reported in these species are serovars 3,7,10,14,15,16,20,22 and 23 for E. tonsillarum [20], and serovars 5, 9, 10 and 18 for E. piscisicarius sp. nov [11,19,20].…”
Section: Discussionmentioning
confidence: 97%
“…The Spa protein has been antigenically divided into SpaA, SpaB and SpaC, and reported to be associated with the serovars of Erysipelothrix strains: E. rhusiopathiae serovars 1a, 1b, 2, 5, 8, 9, 12, 15-17 and 23 possess SpaA; E. rhusiopathiae serovars 4, 6, 11, 19 and 21 possess SpaB [6]; and a different species (Erysipelothrix piscisicarius sp. nov.) possesses SpaC [7]. Furthermore, it has been reported that E. rhusiopathiae clade 1, which is common in marine animals, possesses the spaB gene, whereas E. rhusiopathiae clades 2 and 3, which are common in pig and poultry, possess the spaA gene [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…can be divided into eight different species: Erysipelothrix rhusiopathiae (2, 3), Erysipelothrix tonsillarum (4), Erysipelothrix species 1, Erysipelothrix species 2, and Erysipelothrix species 3 (5), Erysipelothrix inopinata (6), Erysipelothrix larvae (7) and Erysipelothrix piscisicarius sp. nov. (8). Isolates associated with these species were identified in mammals, birds and fish (E. rhusiopathiae, E. tonsillarum and E. species 1, 2, and 3; E. piscisicarius), a vegetable peptone broth (E. inopinata) or insects (E. larvae).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Erysipelothrix is composed of at least five species, E. rhusiopathiae, Erysipelothrix tonsillarum (2), Erysipelothrix inopinata (3), Erysipelothrix larvae (4), and Erysipelothrix piscisicarius sp. nov. (5), the last of which is pathogenic to fish and has been recently proposed as a new member of the genus. Furthermore, the existence of three other species, which are unnamed and tentatively referred to as Erysipelothrix sp.…”
mentioning
confidence: 99%